2018
DOI: 10.1111/sipr.12053
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Thinking Interventions: A Paradigm for Societal Change

Abstract: Social problems such as intergroup conflicts, prejudice, and discrimination have a significant effect on the world's population. Often, to facilitate constructive solutions to these problems, fundamental attitude change is needed. However, changing the beliefs and attitudes to which people strongly adhere has proven to be difficult, as these individuals resist change. In this article, we offer a new and unconventional approach, termed paradoxical thinking, to promote the change of attitudes relevant to social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…For instance, Bruneau and colleagues [9,10] demonstrated that collective blame of Muslims for individual acts of violence, and thereby anti-Muslim hostility, could be reduced by highlighting hypocrisy (e.g., by making a Christian who collectively blamed Muslims realize that they would not collectively blame Christians for acts of violence committed by individual Christians). Similarly, Hameiri and colleagues [23,24] have demonstrated the effectiveness of paradoxical thinking interventions for softening extreme opinions.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, Bruneau and colleagues [9,10] demonstrated that collective blame of Muslims for individual acts of violence, and thereby anti-Muslim hostility, could be reduced by highlighting hypocrisy (e.g., by making a Christian who collectively blamed Muslims realize that they would not collectively blame Christians for acts of violence committed by individual Christians). Similarly, Hameiri and colleagues [23,24] have demonstrated the effectiveness of paradoxical thinking interventions for softening extreme opinions.…”
Section: Introductionmentioning
confidence: 95%
“…Previous research found another, less subtle way of inducing cognitive conflicts via communication to reduce the impact of dominant attitudes in intergroup conflicts: so-called paradoxical thinking interventions (for an overview, see Hameiri et al, 2019). Different from conventional interventions using stereotype-inconsistent communication (e.g., Weber & Crocker, 1983), the messages conveyed through paradoxical interventions are in principle consistent with the recipients' beliefs but amplify and exaggerate these -sometimes even in an absurd form.…”
Section: Paradoxical Leading Questions Reduce Negative Outgroup Attitudes (And Increase Flexibility)mentioning
confidence: 99%
“…While much of the research on psychological barriers has sought to identify them or to evaluate their impact, there have also been numerous efforts aimed at identifying the means by which these barriers might be overcome (Gayer et al ; Paluck ; Paluck and Green ; Shnabel et al ; Bruneau and Saxe ; Vasiljevic and Crisp ; Hameiri and Halperin ; Bruneau, Kteily, and Falk ; Hameiri, Bar‐Tal, and Halperin ). While many articles (directly or incidentally) provide theoretical or conceptual guidance on how to address the problem of psychological barriers, here we review the empirical literature.…”
Section: Overcoming Psychological Barriers: a Review Of Attenuation Imentioning
confidence: 99%
“…Prior work on the scaling of interventions suggests that there is cause for both skepticism and optimism. At a minimum, the creation of consistently effective, evidence‐supported interventions requires painstaking work, with past efforts having required years of pilot testing, data collection, and iterative design (Hameiri, Bar‐Tal, and Halperin ). Ditlmann, Samii, and Zeitzoff () have also pointed out that for interventions to have an impact on large‐scale conflict dynamics, they must have a discernable impact on the behavior of individuals, such as increasing in‐group policing, public advocacy, or political action.…”
Section: Scaling Interventions That Attenuate Intergroup Conflictmentioning
confidence: 99%
See 1 more Smart Citation